An Analysis of Learning Evaluation in the Basic Education Division of the Center for Research and Teaching in Education based on the Pedagogic Model of the Universidad Nacional, Costa Rica - Castillo Cedeño, Ileana (2013)
The research, on which this paper is based, is focused on learning evaluation. The topic selected was: “Operationalization of the University’s Pedagogic Model: An analysis of learning evaluation in four study programs of the Basic Education Division (DEB ) of the Center for Research and Teaching in Education (CIDE), at Universidad Nacional (UNA), Costa Rica”. This research includes an analysis of principles, strategies, and instruments used in the DEB to evaluate learning, with the purpose of contributing to generate evaluation methods that are more coherent with the Pedagogic Model. The information was collected through focal studies and questionnaires responded by teachers and students; the results reported a need of coordination throughout the entire University to fulfill UNA’s Pedagogic Model in terms of learning evaluation.